The effect of copper oxide nanoparticle additives on the rheological and tribological properties of engine oil. Issue 4 (18th January 2021) - Gupta, Harsh; Rai, Santosh Kumar; Satya Krishna, Nippani; Anand, Gagan
Abstract: The rheological and tribological properties of 0.5%, 1.0%, 1.5% and 2% CuO nanoparticles by weight blended in engine oil were studied. Surfactants were used to ensure maximum possible dispersion of the nanoparticles in engine oil. Samples were tested for viscosity, stress, torque and shear rate to be compared with data for just engine oil. Characterization of the Copper Oxide nanoparticles was done using an XRD, FTIR, photoluminescence, UV-Vis spectroscopy and Particle Size Analyzer. Overall, nanoparticle additives seem to result in lower viscosity and lower torque. There was also a force of friction and wear test done on a pin-on-disk machine for all blends. The analysis revealed that 1 wt% CuO blend resulted in low wear and force of friction with improved lubricity of oil. Graphical Abstract: